STUDY OF GUNUNG MERAPI NATIONAL PARK POST 2010 MERAPI ERUPTION MANAGEMENT IMPROVEMENT - , Agus Yulianto ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Mount Merapi, the most active eruptive mountain, erupted in 2010 and caused 82.10 % of Gunung Merapi National Park (GMNP) area that became nonvegetation area. The eruption also degraded many community livelihoods. This research conducted to examine the relevance of the program of GMNP in post-eruption period which is related to area recovery and to make necessary recommendation for improvement, in facing of not completed rehabilitation program to recover the affected area. By the Means-End relationship supporting by PCM, it was resulted that rehabilitation program should be completed according to the planning. In verifying process, the interview was conducted to get opinions related to 5 (five) main issues, consisted of: management plan issue, physical protection facilities issue, community issue, staff training issue and updating GMNP specific data issue. Based on the analysis and discussion, 4 (four) conclusions are resulted. First, GMNP management was not able to complete the rehabilitation programs of post 2010 Mt. Merapi eruption. The problem was caused by 3 (three) factors, consist of: (1) recovery action was not fully accepted by local government, (2) GMNP recovery plan was not suited to the conditions of the affected area, and (3) the activities of the people who tried to gain income by selling natural resources inside GMNP area was not stopped. Second, to improve the effectiveness of GMNP management program, the top priority of GMNP should be placed on responding to rehabilitation with consideration to the preparedness against eruption by updating data which reflect the characteristics of Mt. Merapi integrating data with database systems that should be made easily accessible. Third, to control peoples' activities which were damaging resources inside GMNP area, replacing broken physical protection facilities and proposing additional necessary facilities should be realized. Community involvement and understanding of zoning system should be strengthened. Number of trained staff is necessary to be increased. Fourth, creating a clear management program, synchronizing recovery program among government agencies, increasing community role in GMNP management, collecting and providing Mt. Merapi eruption related data and strengthening networks among stakeholders are the key factors to create recovery program and its implementation.